Produk dakon serbuk kelapa dengan konstruksi kunci las - Dwi Agus Susila (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2023)
Dakon is a traditional Indonesian children's game made of wood, stone, plastic. This traditional game should be preserved. In the design of the product, it will be stylized into an interesting form by applying the methods of exploration, design and realization. The use of the exploration method is aimed at finding the source of ideas that are considered appropriate and then determined as the concept of creation. The design step is to summarize the results of exploration work in the form of selected sketches, then narrowed down into a work design. The next step is realization, a process of working with manual, portable and masinal tools. The realization activities in the wood workshop consist of material preparation, tool preparation, shaping, smoothing, finishing and weld lock construction. The result of the design is a dakon product from coconut wood powder, cobalt, catalyst, resin, nails, alteko glue, two millimeter thick multiplex, six millimeter and twelve millimeter cast iron.  The attractiveness of the product will pay attention to design, form, function, technique, buried with soil, and finishing with water-based paint brand Mowilex which emphasizes changes in the physical form of dakon. Thus the results of the research will be useful for the community, and open new insights into the application of the main materials used. In addition, the creation of this work is also proof that the ability to cultivate art and expression is one of the ways in which the dakon is created.